Sobre las tendencias de la administración. Algunas reflexiones preliminares. (2021)
In relation to the tendencies of the administrative discipline, it is possible to be established that the great challenges of the organizations will be focused clearly in five areas of work, the management, the intellectual capital, the used systems to be more competitive, the international businesses and the promotion of a culture of the emprendimiento. Diverse reasons have appeared to determine in prospectiva which can happen in the companies and which is paper of the administration like discipline that tries to give answer to the questions that can arise in the organizations.